The Qur'an's View of Human Rights (HAM) in the Concept of Freedom and Gender Equality - Fandi Erdiansah; Abu Bakar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article will discuss two main aspects of human rights. The first is the concept of freedom, and the second is the concept of gender equality. This discussion will use an Islamic approach with the method of maudhu'i interpretation. Freedom according to Islam is freedom that is more directed and limited, free but bound not to cross the limits set by Islam. In contrast to freedom according to human rights which tends to be liberal to do the will without limits, while not interfering with the rights of others. While gender equality according to Islam is equality that does not mean exactly the same, the equivalent referred to here is in the value of work done in the eyes of Allah SWT. In Islam men and women have their respective portions in carrying out their rights and obligations. This study dismisses the issue that states that Islam is a religion that is intolerant of human rights, especially in the aspects of freedom and gender equality. However, Islam has its own guidelines to regulate how to implement the concept of freedom and gender equality contained in the Qur'an.